2021
DOI: 10.1016/j.abb.2021.108909
|View full text |Cite
|
Sign up to set email alerts
|

Reduced preload increases Mechanical Control (strain-rate dependence) of Relaxation by modifying myosin kinetics

Abstract: Rapid myocardial relaxation is essential in maintaining cardiac output, and impaired relaxation is an early indicator of diastolic dysfunction. While the biochemical modifiers of relaxation are well known to include calcium handling, thin filament activation, and myosin kinetics, biophysical and biomechanical modifiers can also alter relaxation. We have previously shown that the relaxation rate is increased by an increasing strain rate, not a reduction in afterload. The slope of the relaxation rate to strain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The preload dependence of Ca 2+ handling in cardiac muscle has been studied in isometrically contracting trabeculae ( 13 15 ) and auxotonically contracting myocytes ( 16 ), but it has not yet been examined in isolated cardiac muscle undergoing work-loop contractions. From a mechanistic standpoint, preload has a major role in modulating the ability of cardiac muscle to relax under afterloaded isotonic contractions in trabeculae ( 17 ) and myocytes ( 10 , 18 ), as well as on the mechano-Ca 2+ feedback as recently shown in silico ( 19 ). Hence, it is possible that preload modulates the afterload-dependent Ca 2+ handling observed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The preload dependence of Ca 2+ handling in cardiac muscle has been studied in isometrically contracting trabeculae ( 13 15 ) and auxotonically contracting myocytes ( 16 ), but it has not yet been examined in isolated cardiac muscle undergoing work-loop contractions. From a mechanistic standpoint, preload has a major role in modulating the ability of cardiac muscle to relax under afterloaded isotonic contractions in trabeculae ( 17 ) and myocytes ( 10 , 18 ), as well as on the mechano-Ca 2+ feedback as recently shown in silico ( 19 ). Hence, it is possible that preload modulates the afterload-dependent Ca 2+ handling observed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we found that the relaxation-loading (stretch) was not only necessary, but also sufficient, to modify the relaxation rate without changes in afterload. While Mechanical Control of Relaxation was predicted to be related to crossbridge detachment, the mechanisms underlying this phenomenon remained speculative [ 3 , 4 ]. Modeling performed in these prior studies suggested that the bound crossbridge population was reduced more quickly by stretch, but the experimental protocols did not systematically control for strain rate and time-to-stretch for each trabecula.…”
Section: Discussionmentioning
confidence: 99%
“…After equilibration, isometric twitching was maintained except for a single twitch during each acquisition. For the experimental procedure, we first measured a normal twitch followed by a reference load-clamp twitch by controlling the developed force signal using a custom controller interfacing in SLControl data acquisition software [3][4][5]. The clamp was typically held at 50% of the developed, peak systolic force from the prior "normal" twitch, unless otherwise stated.…”
Section: Intact Cardiac Trabecula Mechanicsmentioning
confidence: 99%
“…The protocol described here utilizes trabeculae and not papillary muscles. The chordae of the papillary muscle induce a series elasticity that can inhibit changes to the MCR 9 . However, the exact placement of the attachments in the muscle is unlikely to impact the measures, because the trabecula length (and diameter) vary substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the data acquisition and analysis can also be applied to cardiomyocytes or other isolated muscle types 1 , 10 . The discussion includes commentary on possible alterations and adaptations to the method, along with limitations, such as caution against utilizing papillary muscles because of the mechanical properties of the chordae 9 .…”
Section: Introductionmentioning
confidence: 99%